Prosodija govorov Terskogo berega Belogo morja: predvrel'nye nabljudenija - Post, Margje (Universitetet i Tromsø, 2001)
The present article presents some preliminary results of the study of some prosodic characteristics of the dialects of Varzuga and Umba, two Northern Russian villages on the Ter Coast of the White Sea. In our recently collected recordings, we observed a number of prosodic characteristics which are assumed to be typical for Northern Russian. Firstly, vowels appear to be relatively short. Secondly, it was often rather difficult to determine the location of the stressed syllables. Thirdly, a tendency to attach a repeating prosodic pattern to each phonological word was observed. Finally, many non-question utterances ended in a rising pitch movement, although the steepness and the height of the Ter rise appear to be less extreme than in, for instance, some Pinega dialects of the Archangel’sk oblast’. Interestingly, the second and third characteristics seem to be closely related. In all but one of the cases with unclear stress patterns, the first syllable was realised with high pitch, immediately preceded and followed by low pitch. This seems to be the result of a tendency to attach a rising-falling pattern to each phonological word.